Insights on Lymphedema Self-Care Knowledge and Practice in Filariasis and Podoconiosis-Endemic Communities in Bangladesh and Ethiopia - Douglass, Janet; Martindale, Sarah; Mableson, Hayley; Jhara, Sanya Tahmina; Karim, Mohammad Jahirul; Rahman, Muhammad Mujibur; Kawsar, Abdullah Al; Khair, Abul; Mahmood, A. S. M. Sultan; Rahman, A. K. M. Fazlur; Chowdhury, Salim Mahmud; Hailekiros, Fikre; et al. (Frontiers in Tropical Diseases, 2021)
Lymphedema is a life-long sequelae to several neglected tropical diseases (NTD). In Bangladesh the main cause is lymphatic filariasis (LF) and Ethiopia is endemic for both LF and podoconiosis. The World Health Organization (WHO) recommends daily self-care including meticulous washing and drying of affected skin and attention to entry lesions, limb exercises and elevation. Adherence to this regime reduces secondary infections which cause disabling episodes of acute dermato-lymphangitis (ADL). Self-care practices must be integrated into family life, supported by community and monitored by health staff; however, little is known about the influence of personal and socio-demographic factors on adherence. People affected by lymphedema (n=272), adult caregivers (n=272), and health workers (n=68) in Bangladesh and Ethiopia were trained in lymphedema management according to WHO recommendations. Surveys on the causes and management of lymphedema were collected at baseline and 24-weeks, and patients completed a daily journal of self-care activities and symptoms. At baseline knowledge on causes and management of lymphedema was greater among health workers (>70%) than patients and caregivers (<20%) in both countries, and there were significant between-country differences in patient reported use of limb washing (Bangladesh = 7.7%. Ethiopia = 51.1%, p = 0.001). At 24-weeks knowledge on lymphedema causes and management had increased significantly among patients and caregivers, there was <70% adherence to limb washing and exercises, but lesser use of limb elevation in both countries. A range of patient characteristics were associated with significant variation in self-care, except for limb washing. Performance of fewer leg exercises was significantly associated with increased age or severe lymphedema in Bangladesh, and with being female or in paid work in Ethiopia. Patient journals recorded ADL symptoms and working days lost due to lymphedema more frequently than were reported by recall during the 24-week survey. Core elements of lymphedema self-care education, training and monitoring are the same for multiple etiologies. This creates opportunities for cross-cutting implementation of integrated service delivery across several skin NTDs. Sustainability will depend on community level ownership and research on factors affecting adherence to lymphedema self-care are urgently needed.